Analisis Keselamatan Dan Kesehatan Kerja Dengan Metode Hazard And Operability (HAZOP) Pada Proyek Pembangunan Perumahan Oleh PT. XYZ - Muhammad Qowiyuddin; Moh. Jufriyanto; Elly Ismiyah (Jurnal Serambi Engineering, 2023)
PT. XYZ is a construction business that manages several projects, including house construction. Through interviews with company HSE personnel, it was revealed that several workplace incidents had occurred, such as falling from scaffolding, getting caught in machinery, inhaling dust particles, tripping, experiencing head injuries, and even being hit. destroyed by matter. The aim of this research is to detect work accidents that may arise as a result of house construction operations carried out by PT. XYZ, using the HAZOP approach. HAZOP is a hazard analysis technique used to ensure safety in new or modified systems by identifying potential hazards or operational problems. This involves assessing the level of hazard and the risks associated with that hazard using probability and consequence analysis. The findings are then categorized using a Risk Matrix. Based on research findings, six types of industrial accidents have high priority risks: material spills, falls from heights, scattered materials, being pierced by metal tips, falling from scaffolding, and dust inhalation. Risk control recapitulation can be done by tidying up unused materials, throwing away unnecessary materials, clarifying work processes, implementing 5S in the work area, wearing complete APD, focusing on work, checking how workers work, and ensuring equipment is in good condition.